Long-term results of nonoperative treatment for uncomplicated acute appendicitis - Kirkil, Cuneyt; Yigit, Mehmet Volkan; Aygen, Erhan (Aves, 2014)
Background/Aims: This study aimed to assess the long-term (>12 months) efficacy of nonoperative treatment (antibiotic administration) in the management of uncomplicated acute appendicitis (AA). Materials and Methods: We surveyed uncomplicated AA patients who elected to undergo nonoperative treatment between 2010 and 2012. A binary logistic regression analysis was performed to identify the critical predictors of recurrence. Age, gender, presence of appendicolith, and white blood cell count on admission were analyzed as possible predictors of recurrence. Results: The median follow-up period of the study was 23 months. Twelve of 118 patients (10.2%) were diagnosed with recurrent appendicitis. Seven were retreated with the same antibiotic protocol and did not show further recurrence. The binary logistic regression analysis revealed statistical significance only for the presence of appendicolith [P=0.001, Exp (B)=0.058, B=-2.845]. Recurrence rate was lower in the presence of appendicolith. Conclusion: Nonoperative treatment of uncomplicated AA is an effective option. Recurrence is rare and it can be addressed efficiently with the administration of a second course of antibiotics. The presence of appendicolith should not discourage physicians from prescribing nonoperative treatment for patients with un-complicated AA.
19th National Surgery Congress -- APR 16-20, 2014 -- Antalya, TURKEY
Keywords: Appendicitis; nonoperative treatment; recurrence